Discovery of DS42450411 as a potent orally active hepcidin production inhibitor: Design and optimization of novel 4-aminopyrimidine derivatives. Issue 20 (1st November 2018) - Fukuda, Takeshi; Ishiyama, Takashi; Katagiri, Takahiro; Ueda, Kenjiro; Muramatsu, Sumie; Hashimoto, Masami; Aki, Anri; Baba, Daichi; Watanabe, Kengo; Tanaka, Naoki
Graphical abstract: Highlights: Hepcidin, a peptide hormone, is a master regulator of systemic iron mobilizations (83 characters). Hepcidin inhibition could be a strategy for treating anemia of chronic disease (80 characters). 4-Aminopyrimidine compound was founded as a hit of Hepcidin production inhibitor (82 characters). Optimization study led to a potent and bioavailable Hepcidin production inhibitor (83 characters). DS42450411 showed serum Hepcidin-lowering effects in an acute inflammation model (82 characters). Abstract: Hepcidin has emerged as the central regulatory molecule in systemic iron homeostasis. The inhibition of hepcidin may be a favorable strategy for the treatment of anemia of chronic disease. Here, we have reported the design, synthesis, and structure–activity relationships (SAR) of a series of 4-aminopyrimidine compounds as inhibitors of hepcidin production. The optimization study of1 led to the design of a potent and bioavailable inhibitor of hepcidin production, 34 (DS42450411), which showed serum hepcidin-lowering effects in a mouse model of interleukin-6-induced acute inflammation.